2019
DOI: 10.1016/j.abb.2019.108165
|View full text |Cite
|
Sign up to set email alerts
|

Role of conserved arginine in the heme distal site of HutZ from Vibrio cholerae in the heme degradation reaction

Abstract: HutZ from Vibrio cholerae is a dimeric enzyme that catalyzes degradation of heme. The highly conserved Arg92 residue in the HutZ family is proposed to interact with an iron-bound water molecule in the distal heme pocket. To clarify the specific role of Arg92 in the heme degradation reaction, the residue was substituted with alanine, leucine, histidine or lysine to modulate electrostatic interactions with iron-bound ligand. All four Arg92 mutants reacted with hydrogen peroxide to form verdoheme, a prominent int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…Despite extensive studies on the mechanism of heme transport from outside to the cytoplasm, proteins that participated in heme utilization remain unknown. Nowadays, Hut (heme utilization) protein has been identified in Vibrio cholerae according to genome sequence and bioinformatics-based predictions (Uchida et al, 2019). Uchida et al have recently purified and characterized HutZ as a heme-degrading enzyme in V. cholerae, which releases iron into the cytoplasm (Uchida et al, 2012).…”
Section: Hut Protein Is Required For Iron Acquisition and Heme Utilizmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite extensive studies on the mechanism of heme transport from outside to the cytoplasm, proteins that participated in heme utilization remain unknown. Nowadays, Hut (heme utilization) protein has been identified in Vibrio cholerae according to genome sequence and bioinformatics-based predictions (Uchida et al, 2019). Uchida et al have recently purified and characterized HutZ as a heme-degrading enzyme in V. cholerae, which releases iron into the cytoplasm (Uchida et al, 2012).…”
Section: Hut Protein Is Required For Iron Acquisition and Heme Utilizmentioning
confidence: 99%
“…Uchida et al have recently purified and characterized HutZ as a heme-degrading enzyme in V. cholerae, which releases iron into the cytoplasm (Uchida et al, 2012). As a unique heme storage protein, HutZ is critical for heme utilization and can cleave heme to biliverdin via verdoheme (Uchida et al, 2019). Besides, it is reported that HutZ is also required for biofilm formation and contributes to the pathogenicity of Edwardsiella piscicida (Shi et al, 2019).…”
Section: Hut Protein Is Required For Iron Acquisition and Heme Utilizmentioning
confidence: 99%
“…6 Consequently, reduction of heme, the first step of heme degradation, is slower at pH values >8.0. 3,23 At lower pH, these interactions are weakened and the reduced heme yield is significantly increased.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Interestingly, the heme degradation rate was increased ∼threefold in the presence of Fe 2+ only (Figure ). Vc HutZ displays pH dependence of heme degradation activity, which is derived from the changes in imidazolate characteristics of the proximal histidine. , Asp132, a highly conserved residue in the HugZ family, forms a hydrogen bond with His170, whose strength is a determinant of the enzymatic activity of Vc HutZ. , In the case of strong interactions between His170 and Asp132, His170 acquires more imidazolate characteristics, which shifts the redox potential of heme iron to a negative value owing to the preference for the oxidized form . Consequently, reduction of heme, the first step of heme degradation, is slower at pH values >8.0. , At lower pH, these interactions are weakened and the reduced heme yield is significantly increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation